A Self Multiplied: Culture and Identity in Relation to Place in Zadie Smith’s White Teeth and Salman Rushdie’s Midnight’s Children - Sahouli, Myriem Nadia (Université d'Ottawa | University of Ottawa, 2016)
This essay examines questions pertaining to transculturality, hybridity, and imaginary homelands, as shown in Zadie Smith’s White Teeth and Salman Rushdie’s Midnight’s Children. Both novels deal with second generation families that have been, or are currently, processing and adapting to their respective postcolonial realities - the case for Rushdie’s Midnight’s Children - or immigrant and second generation families living in London and struggling in the relationship with their hybrid identity markers - such as in the story-line for Smith’s White Teeth. Multiple characters in both Smith and Rushdie’s novels explicitly face coming to terms with these multiple “identity markers” in relation to where they are in the present moment and from whence they and their families have come. Using Smith and Rushdie’s novels as a foundation upon which to consider these issues, this essay explores the realities of hybrid identity, as well as an exploration of the following questions: how do cultural multiplicity and the after-effects of colonization reverberate in families from immediate and future generations? How do questions of identity associated with place adapt and change depending on where one is living? What is considered “home” for an immigrant family living away from their tangible - or not - ancestral place of origin? What becomes of transgenerational memory? This essay explores these questions through the chosen theory and literature.
Keywords: postcolonial literatures; imaginary homelands; intergenerational familial relations; collective memory; identity; transculturality